Preclinical Models of Hepatic Injury: A Comprehensive Review of Chemically, Immunologically, and Pharmacologically Induced Liver Damage in Rat Models - Ravikumar, Lokeshvar; Velmurugan, Ramaiyan; Surendra, Grandhi; Sivasubramanian, P; Reddy, Konatham Teja Kumar; Hanumanthu, Kanaka Durga; Venkateswararao, R; Bellapu, Dhanush; Babu, Ramenani Hari; Swetha, Medishetti (International Journal of Pharmaceutical Investigation, 2026)
The hepatic organ plays a vital role in maintaining the body's homeostasis by facilitating intricate biochemical reactions. Hepatic impairment, a pervasive condition in diverse liver disorders, poses considerable challenges due to its propensity for recurrence and potential to progress to debilitating conditions, including fibrotic scarring, cirrhotic degeneration, and hepatic failure or malignancy. To elucidate the underlying mechanisms and develop efficacious therapeutic strategies, it is crucial to establish a murine model that accurately recapitulates the clinical manifestations and pathophysiological processes of liver damage. The goal of this study is to present a thorough analysis of the many liver damage models, encompassing chemically induced, immune-mediated, alcohol-related, and drug-induced paradigms, with a focus on their methodologies, molecular mechanisms, and relative merits and limitations. By developing robust animal models, researchers can investigate novel hepatoprotective interventions and garner valuable insights into the management of liver damage disorders, thereby enhancing patient care and outcomes.
Keywords: Hepatotoxicity; Rodent Models; Liver Injury Mechanisms; Experimental Pathology; Signaling Pathways.